З історії формування сільських поселень над річкою Бужок на Хмельниччині (за експедиційними дослідженнями) - Гудченко, З. (Народна творчість та етнографія, 2008)
The expedition was held in the following villages in Khmelnitsky oblast: Mytnytsi, Veremiyivka, Khot`kivtsi, Zaruddya. The buildings in these villages represent several building stages which have specific construction materials, constructions, layout schemes, internal and external building of residential and household constructions of peasants’ homestead. Older models of dwellings, remembrances of old residents allowed to get the idea of the traditional village building up and ritual activities concerned with the building of peasant’s hut.